Paparan Iklan Makanan: Hubungan dengan Konsumsi Makanan Tidak Sehat pada Anak Usia 6-23 Bulan Di Indonesia - Sri Ranti Wahyuningsih; Herwinda Kusuma Rahayu; Siska Ariftiyana; Effatul Afifah (Amerta Nutrition, 2026)
Background: High-quality complementary feeding practice can promote healthy growth and development. However, the consumption of unhealthy foods during complementary feeding is common among children in low- and middle-income countries due to massive exposure to food advertising. Unhealthy food consumption may increase the risk of obesity and degenerative diseases among children in the future. Objectives: To analyze the association between the frequency of exposure to food advertising and the frequency of unhealthy food consumption during complementary feeding among children aged 6-23 months in Indonesia. Methods: We conducted a cross-sectional study including 415 children in Indonesia using convenience sampling. Mothers self-reported their frequency of exposure to food advertising in various media and their children’s unhealthy food consumption during the past week using a self-administered online unhealthy food frequency questionnaire. Data were analyzed using a spearman rank correlation test. Results: The mean of total unhealthy food frequency consumption during complementary feeding, including sugar confectionery, frozen treats, baked or fried confections, and salty snack was 18.29 (±9.75) times/week. The mean frequency of exposure to food advertising through electronic, printed, and online media was 5.41 (±5.32) times over the past two weeks. A significant but weak positive association was observed between the frequency of unhealthy food consumption during complementary feeding and exposure to food advertising (r=0.272, p-value <0.001). Conclusions: High exposure to food advertising increases the frequency of unhealthy food consumption during complementary feeding among children. Given the significant impact of such marketing, the government should regulate unhealthy food marketing targeted at mothers.